2017
DOI: 10.13057/nusbiosci/n090104
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and elimination of mercury in Nile Tilapia (Oreochromis niloticus) under an elevated temperature and its ambient concentrations

Abstract: Abstract. Sunardi, Astari AJ, Pribadi TDK, Rosada KK. 2017. Accumulation and elimination of mercury in Nile Tilapia (Oreochromis niloticus) under an elevated temperature and its ambient concentrations. Nusantara Bioscience 9: 18-22. The problems of heavy metal pollution combined with the issue of climate warming has attracted a growing international concern, particularly to those exert very toxic effects to organisms and human, e.g. mercury. There have been evidences for temperature effect on metal uptake, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to El-Sayed (2020), other advantages include resistance to water quality and disease, broad tolerance to environmental quality, efficient ability to form high-quality protein from organic matter, domestic waste, and agriculture. Tilapia can tolerate waters with heavy metal waste (Novebrianto et al 2011;Sunardi et al 2017;Ouma et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to El-Sayed (2020), other advantages include resistance to water quality and disease, broad tolerance to environmental quality, efficient ability to form high-quality protein from organic matter, domestic waste, and agriculture. Tilapia can tolerate waters with heavy metal waste (Novebrianto et al 2011;Sunardi et al 2017;Ouma et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that the accumulation of Hg and Cd in the flesh, liver and kidney of Nile tilapia increased with increasing temperature. The effect of elevated temperature combined with Hg and Cd exposure might have increased fish respiration rate and the uptake of water across the gills (Sunardi et al, 2017). In the same way, high temperature results in a decrease of dissolved oxygen, a situation that fish might be able to tolerate .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies report that metal toxicity in fish is often increased with increasing temperature, and that it is linked to higher metal accumulation. For example, increasing temperature was found to increase cadmiumtoxicity in yellow perch (Baykan et al, 2007;Grasset et al, 2016), lead toxicity inPangasius hypophthalmus , copper susceptibility in fathead minnow (Lapointe et al, 2011), and mercury toxicity in Nile tilapia (Sunardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%